MALFORMASI KAVERNOSA FRONTAL PADA WANITA BERUSIA 36 TAHUN: SEBUAH LAPORAN KASUS - Hardika, Made Sebastian Dwi Putra; Ekasari, Ni Wayan Nurlina; Indrayani, Ida Ayu Sri (PERDOSNI, 2024)
Background: Cerebral cavernous malformation (CCM) is a low-flow neurovascular disease caused by dilatation of capillaries in thin-walled cerebral blood vessels, causing extravasation of blood cells, which is the second highest neurovascular disease. It is a dynamic lesion that can develop over time and the current literature until now still discusses ideal management and effective therapeutic interventions. Case Report: A 36-year-old woman, with no previous medical history, experienced her first ever seizure with pattern of focal to generalized motor onset tonic clonic seizure. Initial head computer tomography (CT) imaging results showed a hyperdense lesion with minimal perifocal edema in the left frontal lobe. Digital subtraction angiography (DSA) showed no evidence of arteriovenous malformation or developmental venous anomaly (DVA). She was diagnosed with CCM type I according to the Zabramski classification based on head magnetic resonance imaging (MRI) result. She was given anti-seizure medications and planned for CCM resection as definitive treatment. Discussion: Diagnosis of CCM is quite more difficult than other neurovascular disease. Head MRI imaging serves as the gold standard modality for diagnostic purposes. Treatment for CCM include conservative treatment, surgery, or radiosurgery. Hemorrhagic in multiple lesions, worse initial neurological findings after hemorrhagic episode, brainstem lesion, and concomitant of other vascular malformations are associated with higher morbidity rates. Conclusion: Early detection of CCM can determine the appropriate treatment for patients. Identification of patients at higher risk can optimize the timing of intervention taken so as to reduce morbidity and mortality rates. Keywords: CCM, cavernous, seizure, malformation